Perceptions of childhood asthma and its control among Malays in Malaysia: a qualitative study - Sukri, Nursyuhada; Ramdzan, Siti Nurkamilla; Liew, Su May; Salim, Hani; Khoo, Ee Ming (Nature Research, 2020)
Children with poor asthma control have poor health outcomes. In Malaysia, the Malays have the highest asthma prevalence and poorest control compared to other ethnicities. We aimed to explore Malay children with asthma and their parents’ perceptions on asthma and its control. We conducted focus group discussions (FGD) using a semi-structured interview guide. Interviews were audio-recorded, transcribed verbatim and analysed thematically. Sixteen children and parents (N = 32) participated. The perception of asthma was based on personal experience, cultural and religious beliefs, and there was mismatch between children and parents. Parents perceived mild symptoms as normal, some had poor practices, raising safety concerns as children were dependent on them for self-management. Conflicting religious opinions on inhaler use during Ramadhan caused confusion in practice. Parents perceived a lack of system support towards asthma care and asthma affected quality of life. Urgent intervention is needed to address misconceptions to improve asthma care in children. © 2020, The Author(s).